IMRiS phase II study of IMRT in limb sarcomas: Results of the pre-trial QA facility questionnaire and workshop. Issue 1 (February 2020) - Simões, R.; Miles, E.; Yang, H.; Le Grange, F.; Bhat, R.; Forsyth, S.; Seddon, B.
Abstract: Introduction: Soft tissue sarcomas of the extremities (STSE) are rare malignancies. We report current UK practice for immobilisation of soft tissue sarcoma of STSE, as part of the initial study set-up within the IMRiS trial, a phase II study of intensity modulated radiotherapy (IMRT) in primary bone and soft tissue sarcoma. Methods: A facility questionnaire (FQ) was circulated to 29 IMRiS centres investigating the variation in immobilisation devices, planning techniques, and imaging protocols. A workshop was held to address concerns raised by centres. It focused on STSE immobilisation and patient set-up. Robustness of patient set-up at each centre was evaluated based on the following criteria: evidence of local set-up audit, calculation of margins based on set-up audit results, imaging frequency, and number of patients treated per centre per annum. Results: Twenty-seven (93%) questionnaires were returned. 30% (8/27) of responders routinely treated STSE with IMRT. The remaining 70% (19/27) had little or no experience with IMRT for STSE. Vacuum bags were the most frequent immobilisation device (9/27), followed by thermoplastic shells (7/27). Nine centres had audited their local set-up; however, only 4 had calculated margins in response to the results. Ten centres were classified as having high level of robustness. Conclusions: Immobilisation devices and planning techniques for STSE are inconsistent across centres. Robustness of set-up is an important tool to ensure quality of results in a multicentre trial setting with such different levels of experience. The IMRiS trial Quality Assurance programme encourages centres to assess robustness of set-up through local audit and subsequent calculation of treatment margins. Implications for practice: This is the first study that used robustness criteria to tailor QA support to individual centres.